Revisiting the role of IL-1 signaling in the development of apical periodontitis - Kento Tazawa; Kento Tazawa; Mariane Maffei Azuma Presse; Hisako Furusho; Philip Stashenko; Hajime Sasaki (Frontiers Media S.A., 2022)
Apical periodontitis (AP) develops as a result of an immune response to pulpal bacterial infection, and various cytokines are involved in the pathogenesis of AP, with Interleukin (IL)-1 being considered a key cytokine. The role of IL-1 in the pathogenesis of AP has been well studied. It is known that IL-1 expression in periapical lesions correlates closely with the development of AP. IL-1 is a potent bone-resorptive cytokine that induces osteoclast formation and activation. Hence, inhibiting its signaling with IL-1 receptor antagonist (IL-1RA) results in a reduction in periapical lesion size. On the other hand, IL-1 is also a central cytokine that combats bacterial infection by activating innate immune responses. Therefore, a complete loss of IL-1 signaling leads to a failure to limit bacterial dissemination and consequently exacerbates AP. In vivo, IL-1 expression is tightly regulated and its signaling is modulated to optimize the immune response. Obesity causes systemic low-grade chronic inflammation and increases the risk of cardiovascular, renal, and other disorders. In experimentally induced AP, obesity significantly increases periapical bone loss, albeit the underlying mechanism remains unclear. Recent technological innovations have enabled more comprehensive and detailed analyses than previously, leading to new insights into the role of IL-1RA in regulating IL-1 signaling, and modulating apical lesion progression in obesity. In this review, we provide a brief overview of the function of IL-1 in AP development, with special emphasis on the latest findings in normal weight and obese states.